A cost-effective beam forming structure for global navigation satellite system multipath mitigation and its assessment. (28th March 2021) - Jia, Qiongqiong; Hsu, Li-Ta; Xu, Bing; Wu, Renbiao
Abstract: Array antenna beam forming has high potential to improve the performance of the global navigation satellite system (GNSS) in urban areas. However, the widespread application of array antennas for GNSS multipath mitigation is restricted by many factors, such as the complexity of the system, the computation load and conflicts between required performance, cost budget and limited room for the antenna placement. The scope of this work is triplicate. (1) The pre-correlation beam forming structure is first suggested for multipath mitigation to decrease the system complexity. (2) With the pre-correlation structure, the equivalence of adaptive beam forming to quiescent beam forming is revealed. Therefore, the computational load for beam forming is greatly decreased. (3) A theoretical model is established to link the benefits of beam forming with GNSS performance improvement in terms of pseudorange quality. The model can be used by industry to balance the aforementioned restrictions. Numerical results with different array settings are given, and a 2 × 2 rectangle array with $0.4λ $ element spacing is suggested as a cost-effective choice in GNSS positioning applications in urban canyon areas.